2020
DOI: 10.1111/pirs.12477
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing farmers' intentions for urban–rural harmony in metropolitan fringes and regional differences therein

Abstract: Farmers' intentions is the intrinsic motivation of the urban–rural harmony development. However, there are few reports examining the factors influencing farmers' intentions. Based on the household questionnaire survey in Pukou district of Nanjing City, the main driving factors to farmers' intentions in metropolitan fringes of China and regional differences therein were quantitatively analysed. The results show that: (i) many factors, especially farmers' education and satisfaction with urban–rural life, influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Regarding H6, these results supported H6. The results are consistent with the results of Xu, D. et al (2020) [78] and Xu, Y. et al (2021) [51]. In general, rural societies are acquaintance-oriented societies, while urban societies are stranger-oriented societies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding H6, these results supported H6. The results are consistent with the results of Xu, D. et al (2020) [78] and Xu, Y. et al (2021) [51]. In general, rural societies are acquaintance-oriented societies, while urban societies are stranger-oriented societies.…”
Section: Discussionsupporting
confidence: 89%
“…As urban farmers leave the society of acquaintances and come to the city to make a living, the anonymity and fickleness of human interactions are strong, and it becomes more and more difficult to establish social trust [79]. The reason for the social distrust of urban migrant farmers is that they are disadvantaged in the distribution of social resources, due to institutional and policy constraints [78]; that is, therefore, it can be hypothesized that high-quality urban integration can enhance social identity and sense of belonging by improving the quality of life, forming solidarity and stable values, and thus weakening the negative effects of emotional deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have underscored various factors influencing farming motivation in different domains (Alimirzaei & Asady, 2011;Dyah & Pinesti, 2021;Fauziyah & Sanudin, 2020;Saleh & Lumintang, 2012). For instance, perceived risk (Han & Li, 2020), farmer's education (Cao et al, 2020), attitudes, and social norms (Rezaei et al, 2018) have been found to determine the farmer's intention. However, the role of flooding relative to farming motivation is lacking in the literature.…”
Section: Hypothesis 1: Flooding Predicts Farmer's Motivation In the A...mentioning
confidence: 99%